Professional identity of an educational psychologist: a case study in Chile - Carrasco Aguilar, Claudia; Baltar de Andrade, María Julia; Bastidas, Natalia; López de Aréchaga, Javiera; Morales, Macarena; López, Verónica (Pensando Psicología, 2019)
Introduction: Educational psychology faces the need to delimit actions and roles, overcome catering for individual differences, and consider the role of school culture. These challenges impact on the identity of educational psychologists, who are currently being hired under the SEP Law in Chile.Objectives: This study described the identity of a school psychologist and the processes of social interaction that lead her to construct this identity, in the context of a Chilean municipal school with its respective micro-political dynamics within the framework of the SEP Law.Methodology: A single case study is conducted through in-depth interviews and one focus group, with a psychologist hired with resources from the SEP Law, teachers and students. Categorical content analyses was performed.Results: There is a tension of the psychologist between being and not being part of the school, as well as peripheral positioning. Her identity is put into tension under a process of negotiation of professional identity.Conclusions: The results are discussed concerning the intensification and disarticulation of work, the ideological complicity, the clinical role of psychology, and the impact of the SEP Law and the micro politics in this scenario.
Keywords: Chile; professional identity; School psychology